An Efficient Amide‐Aldehyde‐Alkene Condensation: Synthesis for the N‐Allyl Amides. Issue 1 (25th January 2016) - Quan, Zheng‐Jun; Wang, Xi‐Cun
Abstract: The allylamine skeleton represents a significant class of biologically active nitrogen compounds that are found in various natural products and drugs with well‐recognized pharmacological properties. In this personal account, we will briefly discuss the synthesis of allylamine skeletons. We will focus on showing a general protocol for Lewis acid‐catalyzed N‐allylation of electron‐poor N‐heterocyclic amides and sulfonamide via an amide‐aldehyde‐alkene condensation reaction. The substrate scope with respect to N‐heterocyclic amides, aldehydes, and alkenes will be discussed. This method is also capable of preparing the Naftifine motif from N‐methyl‐1‐naphthamide or methyl (naphthalene‐1‐ylmethyl)carbamate, with paraformaldehyde and styrene in a one‐pot manner. Abstract : An efficient amide‐aldehyde‐alkene condensation: Synthesis for the N‐Allyl amides : A general protocol for the direct N‐allylation of electron‐poor N‐heterocyclic amides via an amide‐aldehyde‐alkene condensation reaction catalyzed by Lewis acids is summarized. The substrate scope with respect to N‐heterocyclic amides, aldehydes, and styrenes is discussed.